The interaction of intense femtosecond laser pulses with argon microdroplets studied near the soft x-ray emission threshold. (29th December 2017) - Irsig, R; Shihab, M; Kazak, L; Bornath, T; Tiggesbäumker, J; Redmer, R; Meiwes-Broer, K-H
Abstract: The extreme ultraviolet plasma emission from liquid microsized argon droplets exposed to intense near-infrared laser pulses has been investigated. Emission from the warm dense matter targets is recorded in a spectral range in between 16 and 30 nm at laser intensities of 10 14 W cm −2 . Above the emission threshold, soft x-ray radiation exponentially increases with the pulse energy whereby a strong dependence of the yields on the pulse duration is observed, which points at an effective electron collisional heating of the microplasma by inverse bremsstrahlung. Accompanying hydrodynamic simulations reveal the temporal and spatial development of the microplasma conditions. The good agreement in between the measured and calculated emission spectra as well as the extracted electron temperatures confirm that hydrodynamic simulations can be applied in the analysis of strongly excited droplets.